Fishing for complementarities: Competitive research funding and research productivity - Hanna Hottenrott; Cornelia Lawson (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper empirically investigates complementarities between different sources of research funding with regard to academic publishing. We find for a sample of UK engineering academics that competitive funding is associated with an increase in ex-post publications but that industry funding decreases the marginal utility of public funding by lowering the publication and citation rate increases associated with public grants. However, when holding all other explanatory variables at their mean, the negative effect of the interaction does not translate into an effective decrease in publication and citation numbers. The paper also shows that the positive effect of public funding is driven by UK research council and charity grants and that EU funding has no significant effect on publication outcomes.
urn:nbn:de:bsz:180-madoc-353676
Keywords: L31; O3; 330; Research Funding; University-Industry Collaboration; Scientific Productivity